The chemokine RANTES is secreted by human melanoma cells and is associated with enhanced tumour formation in nude mice - Mrowietz, Ulrich; Schadendorf, Dirk (British journal of cancer, 1999)
Modulation of tumour cell growth by tumour-infiltrating leucocytes is of high importance for the biological behaviour of malignant neoplasms. In melanoma, tumour-associated macrophages (TAM) and tumour-infiltrating lymphocytes (TIL) are of particular interest as inhibitors or enhancers of cell growth. Recruitment of leucocytes from the peripheral blood into the tumour site is mediated predominantly by chemotaxins, particularly by the group of chemokines., The aim of this study was to identify peptides released by human melanoma cells with monocyte chemotactic properties. To assure the presence of biologically active mediators, biochemical purification and biological characterization of peptides was based on a detection system dependent on bioactive, monocyte chemotactic activity in vitro. Cell culture supernatants of melanoma cells were fractioned by heparin-sepharose followed by preparative reversed-phase HPLC steps to enrich monocyte chemotactic activity in one single band on a sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) gel. These purified fractions were shown to react with RANTES-specific antibodies in an enzyme-linked immunosorbent assay (ELISA) as well as in Western blot analysis. Amino acid sequencing of the N-terminal protein fragment confirmed 100% homology to the RANTES protein. Further analysis showed that four out of eight melanoma cell lines constitutively expressed and secreted the β-chemokine RANTES as detected by ELISA. The amount of RANTES protein secreted (up to 50 ng ml−1) was about 5-50 times higher than interleukin 8 (IL-8), determined in the same supernatant samples. Tumour necrosis factor α (TNF-α), not, however, IL-2, interferon-γ (IFN-γ), or α-melanocyte-stimulating hormone (α-MSH) was able to up-regulate RANTES and interleukin 8 secretion. Furthermore, higher levels of RANTES secretion in vitro were associated with increased tumour formation upon S.C. injection of six human melanoma cell lines in nude mice. Our data provide evidence that a subset of melanoma cells express mRNA and secrete RANTES protein which may be partly responsible for the recruitment of monocytes, T-cells and dendritic cells into the tumours. However, transplantation experiments in nude mice suggest that effects of RANTES may also benefit tumour progression. Further studies are needed to dissect the underlying mechanisms. © 1999 Cancer Research Campaign